Complex magmatic and impact history prior to 4.1 Ga recorded in zircon from Apollo 17 South Massif aphanitic breccia 73235 - Grange, Marion; Nemchin, Alexander; Timms, Nicholas Eric; Pidgeon, Robert; Meyer, C. (Pergamon-Elsevier Science Ltd, 2011)
Sample 73235 is one of several aphanitic impact melt breccias collected by the Apollo 17 mission at stations 2 and 3 on the slopes of the South Massif. This study presents a detailed investigation of internal structures and U-Pb ages of large zircon grains from this breccia sample. New data combined with the results of previous studies of zircon grains from the same location indicate that most zircon clasts in breccias from stations 2 and 3 formed during multiple magmatic events between 4.37 and 4.31 Ga, although the oldest zircon crystallized at about 4.42 Ga and the youngest at 4.21 Ga. In addition, zircons from the aphanitic breccias record several impact events prior to the 3.9 Ga Late Heavy Bombardment.The results indicate that the zircons probably crystallized at different locations within the Procellarum KREEEP Terrane and were later excavated and modified by several impacts and delivered to the same locality within separate ejecta blankets. This locality became a source of material that formed the aphanitic impact melt breccias of the South Massif during a 3.9 Ga impact. However, the zircons, showing old impact features, are not modified by this 3.9 Ga impact event suggesting that (i) this common source area was located at the periphery of excavation cavity, and (ii) the > 3.9 Ga ages recorded by the zircon grains could date large (basin-forming) events as significant as major later (3.9 Ga) collisions such as Imbrium and Serenitatis.